TRADISI DAN INOVASI MATERIAL FASADE BANGUNAN TINGGI - Jimmy Priatman (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 1999)
Designers of tall building realize that the product of their creativity will impact the built environment for hundred of years. Differ from the past (great pyramids Giza Egypt, the Parthenon Athens- Greece, Cliff Palace Mesa Verde- Colorado), current tall buildings are designed with systems and materials to be properly maintained to enhance the life expectancy of the building. These timeless structures demand a higher level of performance and integration among its major components such as structure, mechanical-electrical, interior and envelope system, which can be extensively monitored and modified. The building facade as